2020
DOI: 10.1149/1945-7111/ab86c4
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Operation Rechargeable Lithium-Air Battery with Acetic Acid Catholyte

Abstract: Lithium-air batteries are expected as next-generation secondary batteries for electric vehicles because of their high energy density. In particular, an aqueous lithium-air battery that uses an aqueous electrolyte has advantages such as a high power density and availability of operation under an air atmosphere. Here, we show the feasibility of an acidic aqueous lithium-air battery that consists of a lithium anode, a lithium-ion conducting liquid interlayer, a solid lithium-ion conductor separator of Li1.4Al0.4G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In addition to aqueous lithium-air batteries, several other advanced aqueous rechargeable batteries have been proposed in the last few decades, including the aqueous lithium-metal chloride [32], aqueous lithium-Fe(CN) 6 3-/Fe(CN) 6 -4- [33], and aqueous Sn/LiCoPO 4 [34] batteries [10]. Among these, aqueous lithium-air battery, the one used in the present study as well, is reported with a high energy density of over 500 Wh kg -1 [27] and a low round-trip overpotential at a high current density of 2.0 mA cm -2 , in air and at room temperature. Nonetheless, a critical change is required in the aqueous lithium-air batteries, i.e., improvement in their coulombic efficiency for lithium deposition and stripping.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to aqueous lithium-air batteries, several other advanced aqueous rechargeable batteries have been proposed in the last few decades, including the aqueous lithium-metal chloride [32], aqueous lithium-Fe(CN) 6 3-/Fe(CN) 6 -4- [33], and aqueous Sn/LiCoPO 4 [34] batteries [10]. Among these, aqueous lithium-air battery, the one used in the present study as well, is reported with a high energy density of over 500 Wh kg -1 [27] and a low round-trip overpotential at a high current density of 2.0 mA cm -2 , in air and at room temperature. Nonetheless, a critical change is required in the aqueous lithium-air batteries, i.e., improvement in their coulombic efficiency for lithium deposition and stripping.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the proposed battery demonstrated good charge and discharge performance at 25 °C and 1.0 mA cm -2 for 8 h. The round trip overpotential at 1.0 mA cm -2 was 0.8 V after 8 h of polarization. The round trip polarization value of this battery at room temperature was considerably lower than the values previously reported for other nonaqueous lithium-air batteries; the values were 1.7 V at 0.64 mA cm -2 for the Li/1M LiClO 4 in EC/LATP/LiOH-LiCl/RuO 2, air cell - [16], 1 V at 0.5 mA cm -2 for the Li/1M LiPF 6 in EC-DEC/LATP/0.1M H 3 PO 4-1M LiH 2 PO 4 /Pt air cell - [26], and 1.6 V at 0.8 mA cm -2 for the Li/[LiFSI-tetraethylene glycol dimethyl ether (G4)]-50 v/v DOL/LAGTP/CH 3 COOH/Pt-C air cell - [27]. The area-specific capacity of 8 mAh cm -2 , which corresponds to 41.5 mAh g -1 based on the weight of the air electrode determined without the titanium mesh, was higher than the value reported for 1.4 mAh cm -2 [26].…”
Section: Resultsmentioning
confidence: 99%
“…The acid aqueous lithium-air battery (ALAB) is not susceptible to contamination from CO 2 . Several types of ALAB with various catholytes such as HAc aqueous solution [9], 0.1 M H 3 PO 4 -LiH 2 PO 4 buffer solution [10], and a 1 M LiNO 3 aqueous solution [11] have been proposed. The water-stable NASICON-type and perovskite lithium-ion conducting solid electrolytes are unstable in strong acid aqueous solution [12]; therefore, weak acid aqueous solutions have been used for ALAB.…”
Section: Introductionmentioning
confidence: 99%
“…The first ALAB was operated at 60 °C because a polyethylene-based polymer electrolyte was used as the interlayer electrolyte to suppress lithium dendrite formation at the lithium electrode [8]. A room temperature ALAB with a HAc catholyte was reported using a lithium dendrite-free interlayer electrolyte by Imanishi and co-workers [9]. One of the issues of ALAB with HAc is the evaporation of the catholyte over a long operation period.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical energy densities of the aqueous lithium-air battery are 1,910 W h kg −1 and 2,004 W h L −1 , which are lower than those of nonaqueous lithium-air batteries but five and two times higher than those of the conventional lithium-ion batteries in terms of mass and volume, respectively (Yamamoto, 2014). The aqueous system with an acidic catholyte does not require a water purification system (Zhang et al, 2010;Soga et al, 2020). As the cell reaction product in this system is soluble in the catholyte, a high-power-density aqueous lithium-air batteries were reported (Imanishi and Yamamoto, 2019).…”
Section: Introductionmentioning
confidence: 99%